Kematian Akibat Covid-19 di Kabupaten Rokan Hulu: Studi Epidemiologi Deskriptif: Studi Epidemiologi Deskriptif - Irwan Muryanto (Jurnal Kesehatan Komunitas, 2021)
Introduction: Since COVID-19 emerged in Wuhan and spread to all corners of the world, many deaths have been reported. Some studies say that several comorbidities exacerbate death suffered previously. Research Objectives: To describe the deaths of patients with COVID-19 in Rokan Hulu Regency. Methodology: It is carried out using a quantitative descriptive method by conducting an explorative analysis. The data used are sourced from epidemiological surveillance data from the Rokan Hulu District Health Office. Deaths due to COVID-19 were estimated according to gender, signs and symptoms, comorbidities, and places of care. Results: A total of 356 out of 5319 people (6.69%) died from COVID-19. The highest distribution of deaths in the female sex was 51.97%. Most of the deaths occurred in patients with COVID-19 with several comorbidities such as pneumonia (35.53%), diabetes mellitus (26.40%), hypertension (15.23%), heart disease (14.21%), kidney failure (8.12%), and other diseases ( 36.55%). Of all deaths, 84.83% died in hospital. Conclusion: Most of the deaths from COVID-19 patients in Rokan Hulu Regency occurred in women, had other comorbid illnesses, followed by pneumonia.